Reflections on Free Logic - Lambert, Karel; Morscher, Edgar; Simons, Peter M. (mentis Verlag, 2017)
Free Logic is an important field of philosophical logic. It appeared first in the 1950s, and Karel Lambert was one of its founders and coined the term. The volume begins with three of Lambert's most recent essays. These papers are followed by a dialogue between Karel Lambert and Edgar Morscher on free logic. The second part of the volume contains papers by Peter Simons and Edgar Morscher on free logic. A systematic and historical survey of free logic with an annotated bibliography of works on free logic completes the book